Respuesta :
Determine the given
2y - x = 8 ⇒ equation 1
y - 2x = -5 ⇒ equation 2
Get y equivalent from equation 2:
y = 2x - 5 ⇒ equation 3
Substitute y = 2x - 5 to equation 1
2(2x-5) - x = 8
Distribute and Simplify
4x - 10 - x = 8
3x = 10 + 8 ⇒ combine like terms by transposing it to other side
3x = 18
x = 6 ⇒ divide both sides by 3 to get the value of x
Substitute the value of x to equation 3
y = 2(6) - 5
y = 12 - 5
y = 7
Answer : x = 6; y = 7
2y - x = 8 ⇒ equation 1
y - 2x = -5 ⇒ equation 2
Get y equivalent from equation 2:
y = 2x - 5 ⇒ equation 3
Substitute y = 2x - 5 to equation 1
2(2x-5) - x = 8
Distribute and Simplify
4x - 10 - x = 8
3x = 10 + 8 ⇒ combine like terms by transposing it to other side
3x = 18
x = 6 ⇒ divide both sides by 3 to get the value of x
Substitute the value of x to equation 3
y = 2(6) - 5
y = 12 - 5
y = 7
Answer : x = 6; y = 7